Accountability and Transparency in Local Government Financial Reporting: An Empirical Study in Indonesia - Badewin; Roosganda Elizabeth; Ana Rusmardiana; Gilbert Rely; Loso Judijanto (Institut Bisnis dan Informatika Kesatuan, 2025)
Growing public demand for clean governance and fiscal responsibility has intensified the need for accountability and transparency in local government financial reporting in Indonesia, a decentralized nation facing challenges in ensuring timely and accurate disclosures. This study aims to investigate the level of accountability and transparency in local government financial reporting and identify institutional, regulatory, and technological factors influencing reporting quality. Using a quantitative approach, the research analyzes secondary data from 187 local government financial statements audited by the Indonesian Supreme Audit Board between 2018 and 2022, employing regression analysis to assess the impact of internal control effectiveness, audit opinions, electronic government systems, and financial management competencies. The findings reveal that robust internal control systems and favorable audit opinions significantly enhance reporting quality, while electronic government platforms improve both transparency and timeliness. The interaction between electronic government systems and financial management competencies further strengthens transparency, though disparities in technical capacity and leadership commitment create regional inconsistencies. This study concludes that institutional quality, digital innovation, and skilled human resources are vital for advancing financial accountability and transparency, offering actionable insights for policymakers to strengthen governance and rebuild public trust through credible reporting practices.